DIMENSI EKONOMI DALAM IMPLIKASI PERPAJAKAN DI INDONESIA - Dini Vientiany; Fahriza Alyanisa; Shafa Sizli Kania; Siti Zuhairoh Ritonga (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to find out more about the economic dimensions of tax implications in Indonesia. This research uses a qualitative approach with data collection techniques through document analysis to explore the economic dimensions of taxation in Indonesia. Based on the results of research and data analysis that has been carried out, this research shows that the taxation system in Indonesia has an important role in encouraging economic growth and improving people's welfare. The increase in tax revenues in 2021, especially from the Income Tax (PPh) and Customs Tax sectors, indicates economic recovery after the COVID-19 pandemic. However, a complex tax system and high ETR can hinder investment and business performance.